Electronic manifestation of cation-vacancy-induced magnetic moments in a transparent oxide semiconductor: anatase Nb:TiO2 - Zhang, Shixiong; Ogale, Satishchandra B.; Yu, Weiqiang; Gao, Xingyu; Liu, Tao; Ghosh, Saurabh; Das, Gour P.; Wee, Andrew T. S.; Greene, Richard L.; Venkatesan, Thirumalai (Advanced Materials, 2009)
Nb-doped anatase TiO2 thin films grown by pulsed-laser deposition show Kondo scattering in elctronic-transport measurements, providing evidence for the formation of magnetic moments. The origin of magnetism is attributed to cation (Ti) vacancies, confirmed by X-ray absorption spectroscopy and first-principle calculations. The Ti vacancies are controlled by oxygen partial pressure during growth.